2017
DOI: 10.1139/cjfr-2016-0468
|View full text |Cite
|
Sign up to set email alerts
|

Does intensified boreal forest harvesting impact soil microbial community structure and function?

Abstract: Intensified biomass harvesting in northern forests could potentially negatively impact soils. This study measured microbial community structure and function to assess the impacts of intensified biomass removal on soil from a managed northern jack pine (Pinus banksiana Lamb.) forest in Ontario, Canada. Four clear-cut harvesting removal intensities were compared with uncut controls and mature, fire-regenerated forest reference plots: stem-only removal, full-tree biomass removal, full-tree biomass with stump remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Consistent with Chen and Wise (1999), we also found carnivorous spiders and ground beetles to increase with prey availability. The lower abundance of fungivorous mesofauna and rove beetles may also result from the microbial biomass decline observed in disturbance treatments (Smenderovac et al, 2017). In contrast, our analysis suggests that negative effects of increasing predators on their prey in disturbance treatments were not significant.…”
Section: Indirect Effects Of Disturbancementioning
confidence: 55%
See 2 more Smart Citations
“…Consistent with Chen and Wise (1999), we also found carnivorous spiders and ground beetles to increase with prey availability. The lower abundance of fungivorous mesofauna and rove beetles may also result from the microbial biomass decline observed in disturbance treatments (Smenderovac et al, 2017). In contrast, our analysis suggests that negative effects of increasing predators on their prey in disturbance treatments were not significant.…”
Section: Indirect Effects Of Disturbancementioning
confidence: 55%
“…Increasing soil temperature typically increases litter decomposition rate (Anderson, 1991;Hobbie, 1996;Fierer et al, 2005), but higher temperature can also lower moisture which is likely to decrease microbial activity and therefore decomposition (Schimel et al, 1999;Wan et al, 2007;Butenschoen et al, 2011). Working in the same sites used in this study, Smenderovac et al (2017) documented lower microbial biomass in the disturbance treatments compared to the mature forest. We effectively found lower litter mass loss in these treatments.…”
Section: Indirect Effects Of Disturbancementioning
confidence: 64%
See 1 more Smart Citation
“…As there was also little evidence of changes to soil quality or pH in these sites, the lack of community response to ash addition is likely because the changes to soil characteristics were minor to non-detectable 18 . It has been demonstrated that harvesting can cause detectable community changes 17 . While the quantities of wood ash added in this study are considered reasonable operational amount, they might have been insufficient to mitigate stresses (e.g., calcium and magnesium depletion, high acidity) and create further community shifts.…”
Section: Discussionmentioning
confidence: 99%
“…Soil arthropod, bacterial and fungal communities are known to be responsive to differences in moisture, pH and calcium levels 16 . While harvest disturbance alters moisture, pH and calcium which results in stark changes to microbial community composition from uncut forest systems, increases to harvesting intensity can be small and undetectable 17 . The effects of wood ash amendment are likely also small; a recent study of sites across Canada showed inconsistent responses in soil quality metrics due to wood ash amendment 18 .…”
Section: Introductionmentioning
confidence: 99%